Astragalus polysaccharides attenuate pulmonary fibrosis by inhibiting the epithelial-mesenchymal transition and NF-κB pathway activation - Zhang, Rui (Int J Mol Med, 2020)
Astragalus polysaccharides (APS), the active ingredients isolated from the plant Astragalus, have been reported to have numerous biological activities, including anti-inflammatory and antitumor activities. However, the effect of APS on pulmonary fibrosis (PF) remains unknown. The present study aimed to evaluate the protective effect of APS against PF and to explore its underlying mechanisms by using in vivo and in vitro models. A mouse in vivo model of bleomycin-induced PF and an in vitro model of transforming growth factor β1 (TGF-β1)-stimulated human lung epithelial A549 cells were established. Histopathologic examination and collagen deposition were investigated by hematoxylin and eosin staining and Masson staining, and by detecting the hydroxyproline content. The expression of related genes was analyzed by western blotting, reverse transcription-quantitative (RT-q) PCR, immunofluorescence and immunohistochemistry. The results from the in vivo mouse model demonstrated that treatment with APS could ameliorate collagen deposition and reduce fibrotic area and hydroxyproline content in the matrix. Furthermore, APS significantly inhibited the epithelial-mesenchymal transition (EMT), as evidenced by an increased level of E-cadherin and a decreased expression of vimentin and alpha smooth muscle actin. Furthermore, APS treatment significantly decreased TGF-β1-induced EMT and NF-κB pathway activation in vitro. The results from the present study provided new insights on PF regression via the anti-fibrotic effects of APS.